Limonene Extraction From Citrus Waste As An Eco-Friendly Solvent: Conventional And Non Conventional Techniques - A Review - Waskito, Andreas Gangsar Bayu; Armita Sari, Pande Made Nova (Innovative: Journal Of Social Science Research, 2025)
Limonene is a tepenoid compound found abundantly in orange peel waste that can be used as a green solvent due to its hydrophobic or nonpolar nature to reduce the use of chemical solvents that are harmful to the environment. This study aims to review factors that support the limonene extraction process such as extraction method, temperature, power, extraction time and also solvent ratio. This article is compiled based on literature obtained from Google Scholar and Pubmed using the keywords "limonene extraction" and "citrus peel essential oil". The articles used are articles with a time span of 10 years, namely from 2015 to 2025 with inclusion criteria in the form of articles in Indonesian or English that explain the limonene extraction method in full. The extraction methods used include steam distillation, hydrodistillation, Microwave Assisted Extraction (MAE), Ultrasound Assisted Extraction (UAE), and Microwave Assisted Hydro Distillation (MAHD). The MAHD method yielded the highest limonene content of 98.416% with a sample-to-solvent ratio of 1:3 and a microwave power of 300 W for 45 minutes. The MAHD method was the most effective extraction method due to its time and process efficiency, the use of environmentally friendly solvents, and high yields.